Perancangan Sistem Manajemen Mutu ISO 9001:2008 di Sebuah Perusahaan Pengecoran Aluminium - Florencia Liliani Putri; I Nyoman Sutapa (Jurnal Titra, 2016)
The study was conducted at the manufacturing company of the aluminum casting that produces hoist cyilinder and power take off. The Company was not yet fully implemented the quality management system ISO 9001:2008. Based on an initial gap analysis, it is known that the company has only implemented the quality management system requirements by 37.21%. The purpose of this study is to fill the existing gap. The research results showed that 60.46% the quality management system requirements have been met.